1993
DOI: 10.2307/1939935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insect Herbivory and Fungal Endophyte Infection on Competitive Interactions among Grasses

Abstract: Interactions among plants may be influenced by pests or parasites that differentially affect one competitor. The purpose of this study was to determine the effects of fungal parasitism and insect herbivory, alone and in concert, on plant competitive interactions. The effects of fungal endophyte (Acremonium spp.) infection and fall armyworm (Spodoptera frugiperda) herbivory on competitive interactions in one-and two-species mixtures of the grasses tall fescue (Festuca arundinacea), red fescue (F. rubra), and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(166 citation statements)
references
References 40 publications
(64 reference statements)
2
163
0
1
Order By: Relevance
“…This phenomenon is particularly well documented in the agricultural grasses Festuca arundinacea and Lolium perenne infected by Neotyphodium endophytes where these metabolites cause toxicosis in cattle and sheep (Rowan, 1993 ;Bacon, 1995). Infected plants also often show enhanced growth and increased competitive abilities (Clay et al, 1993 ;Malinowski et al, 1997), as well as increased resistance to drought, pests and\or pathogens (Kimmons et al, 1990 ;Gwinn & Gavin, 1992 ;West, 1994 ;Schuster et al, 1995 ;Elbersen & West, 1996).…”
Section: mentioning
confidence: 99%
“…This phenomenon is particularly well documented in the agricultural grasses Festuca arundinacea and Lolium perenne infected by Neotyphodium endophytes where these metabolites cause toxicosis in cattle and sheep (Rowan, 1993 ;Bacon, 1995). Infected plants also often show enhanced growth and increased competitive abilities (Clay et al, 1993 ;Malinowski et al, 1997), as well as increased resistance to drought, pests and\or pathogens (Kimmons et al, 1990 ;Gwinn & Gavin, 1992 ;West, 1994 ;Schuster et al, 1995 ;Elbersen & West, 1996).…”
Section: mentioning
confidence: 99%
“…Other types of interactions, taking into account a main host grass (Festuca or Lolium) and others grasses living in a common space, were conduced by Clay et al (1993), who analized changes resulting from these plant-plant interactions in insect control and presence of endophytic fungi. They analysed the effects of a member of the genus Acremonium in relation to attacks of S. frugiperda larvae to the tall fescue F. arundinacea and the red fescue F. rubra grown separately or mixed with other grasses.…”
Section: Genetic and Environmental Modifications Influencing Insect Cmentioning
confidence: 99%
“…There have been several studies investigating both intraspecific and interspecific competition in F. arundinacea under controlled environmental conditions that have shown that infected plants are better competitors both with and without herbivory (Clay 1990a(Clay , 1997aHill et al 1991;Marks et al 1991;Clay et al 1993;Clay and Holah 1999). This may explain why attempts to establish endophyte-free pastures from highly uninfected seed have at times been unsuccessful as a few seeds in the mix will contain live endophytes.…”
Section: Previous Population and Community-scale Studiesmentioning
confidence: 99%